Fabrication and impact properties of short abaca (Musa textile Nee) fiber-reinforced high impact polystyrene (HIPS) composite - Hadi, Agung Efriyo; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Mohd Dahlan, Khairul Zaman; Usman, Mustofa (2009)
In the recent times, there has been an ever-increasing interest in green composite materials are for its applications in the field of industries, automotive, household etc and in many other fields. In this paper, fabrication of Abaca (Musa textile Nee) fibre reinforced High Impact Polystyrene (HIPS) composites using Maelic Anhydried as coupling agent and impact modifier (cyclo resin) have been reported. A systematic approach for processing of composites is presented. The abaca fibres were accomplished in short size and particle size of 200 (micron). The composites with various compositions of design research; ranging 30, 40, and 40 %wt for abaca fibre, 1, 2, and 3 %wt for Maelic Anhydried and 4, 5, and 6 %wt for impact modifier were prepared for evaluation. Productions of the composites use the rolling machine then continue with hot press machine for measurement size. These samples were then evaluated for laboratories test. It was found that the composites with the content of the composition above showed different the impact properties.